Design and study of a switch reactor for Central Queensland SWER system - Hezamzadeh, M.; Hosseinzadeh, N.; Wolfs, Peter (IEEE, 2008)
Single Wire Earth Return (SWER) systems are awidely applied, low cost electrification method used inmany rural areas. In Central Queensland a single SWERsystem supplying approximately 100kW may extend morethan 300km. Many SWER systems include shunt reactorsto control the effects of the line charging capacitance. Oneeffect, the Ferranti effect, causes the line voltage to risewith the distance. In three phase distribution systems thiseffect is not visible but in SWER systems, this effect makesit difficult to maintain the consumers supply within theacceptable regulation range. As the second effect, theloading of the SWER system supply transformer increases.Controllable shunt reactors are used as one solution to theaforementioned problems.Stanage Bay feeder in Central Queensland area has beenchosen for the installation of the designed shunt reactor.Stange Bay feeder is supplied by an isolating transformerwith the total capacity of 150kVA and the voltage level of22kV.Using the Stanage Bay feeder, this paper details theprocess of design and simulation of a suitable switchreactor. This step has been carried out by firstly, thedesign of the switch reactor and secondly, the propermodelling of the designed reactor for the voltageregulation studies.